PEDAGOGICAL APPROACHES IN THE ONLINE TRAINING OF BASIC EDUCATIONPROFESSIONALS TO FAVOR INCLUSION: A SCOPING REVIEW - Perez, Daniela Jordao Garcia [UNESP] (2023)
This study aims to understand the evidence and gaps in pedagogical and methodological approaches in online teacher training for the inclusive education of Students with Special Educational Needs (SEN) and compliance with national policies. The protocol of the Joanna Briggs Institute (JBI) was used to conduct a scoping review on articles published between 2019 and May 2023. Three electronic databases, including two national and one international, were searched. A total of 238 articles were identified. Applying the inclusion and exclusion criteria, only three articles were selected for analysis based on the explicit questions stated in the text. The analysis included evidence related to the methodological approach, the results, and recommendations for training processes. The results revealed that only one article clearly indicates the approach used in teacher training, but all three highlight the collaborative work between mainstream classroom teachers and specialized teachers as crucial for the development of an inclusive culture in the school context. The evaluation of all stages of the teacher training process, from its conception to the follow-up of graduates, is considered relevant to underpin the reflexive process of both the involved team and the teachers in training.